Partial discharges measurement by UHF method - Malešević, Nevena; Žarković,; Ilić, Denis; Jovanović, Đorđe (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
The unconventional UHF (Ultra High Frequency) method of measuring partial discharges (PD) is based on measuring electromagnetic waves (EM) in the UHF frequency band (300-3000) MHz, using appropriate antennas. This method is unconventional, but is widely accepted due to the possibility of application in plants in the online mode and quick review (screening) of the plant. Also, this method is characterized by a high degree of measurement sensitivity and relatively good resistance to interference. As the PD pulses are of very short duration, of the order of nanoseconds, they generate an electromagnetic pulse whose spectrum reaches GHz. In the conductive structures of an object, these pulses induce electromagnetic wave transients. A certain type of antenna has the ability to receive these transient waves. The paper gives an example of field and laboratory tests that show the correlation between the detection of PD using UHF devices and devices based on the principle of acoustic detection. The possibility of reliable detection of partial discharges in plants in operation has been proven.
Keywords: partial discharges, UHF test, unconventional method, acoustic test, switchgear, instrumental transformer